Qualitative evaluation of selected social factors that impact sexual risk-taking behaviour among African students in Kwazulu-Natal, South Africa - Ndumiso Daluxolo Ngidi; Sibusiso Moyo; Thobile Zulu; Jamila Khatoon Adam; Suresh Babu Naidu Krishna (Taylor & Francis Group, 2016)
Background: The incidence of HIV and AIDS continues to be a source of great concern within universities in South Africa. Furthermore, university students constitute an important community in the intervention against the HIV/AIDS epidemic. Students in the age group of 15-24 years are at a greater risk of HIV infection than any other group in the country; yet, little is known about why they continue to engage in risky sexual practices. Objectives: This study was designed to explore the sexual behaviour of students in a metropolitan Durban University of Technology in KwaZulu-Natal to understand the social factors underlying their risk of HIV infection. Methods: This is a qualitative study that used cluster sampling where the population was stratified by campus and faculty. The study population was selected using a standard randomization technique. This was a part of a multi-phased research project aimed at providing a sero-prevalence baseline and an analysis of risk-taking behaviour at a Durban University of Technology in the eThekwini Metropolitan Municipality area. Results: The study highlights peer pressure among students as an influence in promoting high-risk sexual behaviour. Within this context, the findings revealed that university students lack the ability to negotiate risk-aware decisions especially regarding sexual relationships. Conclusion: This study draws attention to the perspectives of African university students regarding their risk-taking sexual practices and selected factors which influence such behaviour. The findings are not exhaustive in exploring contextual antecedents that shape students' sexual practices. However, they provide an important basis in understanding key factors which expose students to HIV infections. The study provides insights into opportunities for further studies as well as preventative implications.